A Randomized, Double Blind, Placebo-Controlled Human Clinical Trial On The Effects Of Sacha Inchi (Plukenetia Volubilis L.) Oil Supplementation In Hyperglycaemia, Hypertension And Hyperlipidaemia Patients - Mhd Rodzi, Nur Anis Raihana (2024)
The incidence of hyperglycaemia, hypertension and hyperlipidaemia (3Hs) have been prevalent in many developed and developing countries. Sacha Inchi oil (SIO) is a rich source of plant-based omega-3, 6, and 9 polyunsaturated fatty acids with promising health effects. However, the effects of SIO as complementary medicine among the 3Hs individuals are narrowly investigated. The present randomised, doubleblind, placebo-controlled human clinical trial aimed to explore the effects of SIO supplementation on (1) glycaemic control; (2) BPs; (3) lipid profiles; (4) inflammatory status; (5) oxidative stress; (6) circulating arterial calcification biomarkers; (7) anthropometry measurements; (8) quality of life; (9) mental health status; and (10) compliancy and tolerability among 3Hs patients. Fifty-four (n=54) 3Hs patients were recruited from Specialist Day Care Clinic, Pusat Perubatan USM Bertam, and randomised into two groups: the SIO group (n=27) (received 1000mg of SIO soft gel per day) or placebo group (n=27) (received 1000mg corn oil soft gel for 12 weeks). Fasting blood samples were collected at baseline and post week-12 to assess clinical and laboratory biochemical markers.